The Philosophy of "Tri Hita Karana": A Balinese Philosophical Framework for a Sustainable Human-Nature-Divine Relationship - Wijaya Wijaya; Chenda Dara; Sokha Dara (Journal of Humanities Research Sustainability, 2025)
Background. The rapid ecological degradation occurring across Southeast Asia has intensified scholarly interest in indigenous philosophical systems that articulate holistic models of human environment relations. Tri Hita Karana (THK), a foundational Balinese philosophical framework emphasizing harmony among humans, nature, and the divine, has increasingly been invoked in discussions of sustainability; however, empirical and conceptual examinations of how THK can inform contemporary environmental ethics remain limited. Purpose. This study aims to analyze THK as a philosophical foundation for sustainable practices by exploring its metaphysical assumptions, socio-cultural manifestations, and potential integration into modern sustainability paradigms.   Method. The research employs a qualitative hermeneutic design, combining textual analysis of Balinese lontar manuscripts, ethnographic documentation, and thematic synthesis of secondary environmental studies. Results. The findings reveal that THK offers a distinctive triadic model of relational ethics parahyangan (divine harmony), pawongan (social harmony), and palemahan (ecological harmony) that collectively provide normative guidance for sustainable living and resource management. These principles demonstrate compatibility with contemporary ecological frameworks while offering culturally grounded motivations for environmental stewardship. Conclusion. The study concludes that the THK philosophy constitutes a viable ethical foundation for sustainable development, supporting integrative approaches that blend spiritual values, communal responsibility, and ecological awareness. The philosophical coherence and cultural rootedness of THK suggest strong applicability in policy design, environmental education, and community-based conservation efforts.